Vapor Phase Electrochemistry: The Missing Science - Turner, David (Journal of Scientific Exploration, 2023)
Several aspects of physics have been adversely effected by the fact that vapor phase electrochemistry has proved impossible to quantify. By the end of the 19th century, physicists had encountered several strange observations that appeared to involve chemistry. Eventually, it was realized that, in a moist gas, no rate process involving ions is quantifiable since we possess no valid relationship between the concentrations of electrolytes and their thermodynamic activities. There are both technical and societal reasons for this problem. Until both problems have been addressed, no reliable quantitative conclusions can be drawn for any system where ionic electrostriction in a moist gas is important. The most obvious consequences of the missing science are misconceptions concerning naturally contained air plasmas such as ball lightning, tornadic lights, and unpredictable flying objects (UFOs). None of these phenomena violates any known law of physics, but this only becomes clear once the absence of applicable, strictly valid theories is accepted. Fortunately, partial solutions to the problem exist if use is made of qualitative arguments. Using this approach, it can be seen that all the apparently anomalous characteristics of atmospheric plasmas result from a balance between different physical and chemical driving forces. A better understanding of the chemical consequences of electrostriction should have two long-term benefits. One relates to understanding the corrosive properties of high-pressure steam. The other concerns the specific chemical processes that stabilize air plasmas. If stable air plasmas could be simulated, a plentiful supply of carbon-free energy would become available.